2011
DOI: 10.1007/s10792-011-9449-5
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic subconjunctival entrapment of a cilium

Abstract: We report an unusual case of asymptomatic subconjunctival entrapment of a cilium. A 64-year-old man presented with a 3 month history of a painless black line in the conjunctiva of the left eye, and slit-lamp examination revealed a cilium under the conjunctiva. The patient remained asymptomatic without conjunctival edema or hyperemia during a 2 week follow-up. To the best of our knowledge, this is the first report of an asymptomatic cilium inside the subconjunctival space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Conjunctival scarring predisposes entrapment of cilia by making folds and blind recesses in the conjunctiva. 9 In our case patient reports irritation and foreign body sensation from many months along with history of rubbing of lower eyelid.Cilia entrapment and constant rubbing have predisposed to conjuctival inflammation. Long term inflammation and associated conjuctival scarring have further predisposed to symblepheron formation.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Conjunctival scarring predisposes entrapment of cilia by making folds and blind recesses in the conjunctiva. 9 In our case patient reports irritation and foreign body sensation from many months along with history of rubbing of lower eyelid.Cilia entrapment and constant rubbing have predisposed to conjuctival inflammation. Long term inflammation and associated conjuctival scarring have further predisposed to symblepheron formation.…”
Section: Discussionmentioning
confidence: 65%
“…Mimura et al, reported an asymptomatic subconjunctival cilium without hyperemia or edema. 9 George and Silvestri reported subconjunctival cilia with recurrent foreign body irritation. 11 In our case, the patient had complaints of irritation and foreign body irritation with history of rubbing leading to long term inflammation and symblepheron formation.…”
Section: Discussionmentioning
confidence: 99%
“…[12345] A punctual FB can cause secondary ocular inflammation. [4] Eyelashes are reported to enter the upper punctum three times more frequently than the lower punctum.…”
Section: Discussionmentioning
confidence: 99%